Analysis of Conventional Bicycle Assembly Transformed into an Electric Bicycle Using a BLDC Electric Motor - Sudirman Yahya; Nofiansyah (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Along with the increasing problem of oil price volatility, vehicles with alternative fuels are the right vehicles to use at this time. Electric bicycles are one of the vehicles that use alternative fuels. Electric bicycles use battery power as a power source. Electric bicycles consist of two main parts, namely bicycles and electrical components. Bicycles are made through a sequence of planning processes and then assembling bicycle components. Electrical components consisting of batteries, controllers, gas grips, and electric motors are assembled and connected to one bicycle.